Description of a new species of the leafhopper genus Tambocerus (Hemiptera: Cicadellidae: Deltocephalinae) from Guizhou, China - Yao, Binbin; Dietrich, Christopher H.; Xing, Jichun (Zootaxa, 2022)
A new leafhopper species, Tambocerus fanjingensis sp. nov., is described and illustrated from Guizhou Province, China. A checklist of the Chinese species of Tambocerus is provided and a key based on the male genitalia is given to distinguish the Chinese species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).